VOLTAGE-DEPENDENT OPENING OF HCN CHANNELS: FACILITATION OR INHIBITION BY THE PHYTOESTROGEN, GENISTEIN, IS DETERMINED BY THE ACTIVATION STATUS OF THE CYCLIC NUCLEOTIDE GATING RING - Rozario, Anjali. O. (2009)
Investigation of the mechanistic bases and physiological importance of cAMP regulation of HCN channels has exploited an arginine to glutamate mutation in the nucleotide-binding fold, an approach critically dependent on the mutation selectively lowering the channel’s nucleotide affinity. In apparent conflict with this, in intact Xenopus oocytes, HCN and HCN-RE channels exhibit qualitatively and quantitatively distinct responses to the tyrosine kinase inhibitor, genistein – the estrogenic isoflavonoid strongly depolarizes the activation midpoint of HCN1-R538E, but not HCN1 channels (+9.8 mV ± 0.9 versus +2.2 mV ± 0.6) and hyperpolarizes gating of HCN2 (−4.8 mV ± 1.0) but depolarizes gating of HCN2-R591E (+13.2 mV ± 2.1). However, excised patch recording, X-ray crystallography and modeling reveal this is not due to either a fundamental effect of the mutation on channel gating per se or of genistein acting as a mutation-sensitive partial agonist at the cAMP site. Rather, we find that genistein equivalently moves both HCN and HCN-RE channels closer to the open state (rendering the channels inherently easier to open but at a cost of decreasing the coupling energy of cAMP) and that the anomaly reflects a balance of these energetic effects with the isoform specific inhibition of activation by the nucleotide gating ring and relief of this by endogenous cAMP. These findings have specific implications with regard to findings based on HCN-RE channels and kinase antagonists and general implications with respect to interpretation of drug effects in mutant channel backgrounds.